Computational Assessment of the Efficacy of Oxidation-Resistant Iridium Coatings for Multiple Principal Component Rhenium Substitutes. (December 2020) - Liu, Helena; Asta, Mark; van de Walle, Axel
Graphical abstract: Abstract: Rhenium is an advanced engineering material valued for its performance under rapid thermal cycling to high temperatures. Due to rhenium's high cost, alternatives are actively being sought, and hexagonal close packed multiple principal component alloys consisting of Mo, W, Ta and Ru have been previously identified as a promising candidate. Here we assess whether the use of iridium coatings, a widely adopted approach to limit the oxidation of Re, can also be used with this candidate alloy. Specifically, we quantify, through atomistic computations based on density functional theory, the relative diffusion rates of the constituent elements through the protective Ir coating, which is known to be a dominant failure mechanism.